Traditional Practices and Beliefs in Post-partum Care: Tribal Women in Maharashtra. Issue 1 (June 2018) - Dehury, Ranjit Kumar; Pati, Ashalata; Dehury, Parthsarathi
Post-natal care and traditional post-partum practices have important bearings in maternal and child health outcomes. A study was conducted to understand the traditional post-partum practices by the tribal mothers in rural areas of Vikramgad taluka, Maharashtra, India. A qualitative methodology has been adopted by using data collection methods like focus group discussions (FGDs) and in-depth interviews. Key informant interview methods were adopted to understand the mother's post-natal diet, personal hygiene, physical activity and rest, neonatal feeding and care practices during pregnancy. Respondents reported that the mother in the post-partum period, locally called balantini, has to follow certain specific practices regarding diet, hygiene and rest to keep herself and her baby healthy. The study reflects on how traditional beliefs and practices affirm gender biases, traditional beliefs and practices when it comes to new mothers and their care. To address the health needs of these 'last women', the government and civil society have to work for the reduction of poverty, removal of harmful practices, gender equity and empowerment.